MANAGEMENT OF REGIONAL INNOVATIONINFRASTRUCTURE WITH THE USE OF NEURAL NETWORKS - M. A. Kosukhina (Дискурс, 2019)
The article provides an interpretation of the concept of regional innovation infrastructure, systematizes main approaches to managing regional innovation infrastructure and proposes a new approach to management based on business metrics of regional innovation infrastructure, combining factor, process and system approaches. This method allows to solve problems related to lack of systematization of mechanisms of coordination, development and use of infrastructure with strategic directions of the region, limited capacity to create and implement high-tech IT solutions to ensure the digitization of the regional economy, lack of documentation support for regulated business processes in the existing innovation practices, lack of clearly regulated objective business metrics of the regional innovation infrastructure that support innovative process at all its stages. The article also develops a model for managing the innovation infrastructure of the region using neural networks based on the hybrid approach proposed.